Analysis of vertical marginal discrepancy in feldspathic porcelain crowns manufactured with different CAD/CAM systems: Closed and open - Kricheldorf, Fabio (Eur J Dent, 2018)
OBJECTIVE: The objective of this study is to compare the marginal adaptation of feldspathic porcelain crowns using two computer-aided design/computer-aided manufacturing systems, one of them is open and the other is closed. MATERIALS AND METHODS: Twenty identical titanium abutments were divided into two groups: open system (OS), where ceramic crowns were created using varied equipment and software, and closed system (CS), where ceramic crowns were created using the CEREC system. Through optical microscopy analysis, we assess the marginal adaptation of the prosthetic interfaces. The data were subjected to the distribution of normality and variance. The t-test was used for the analysis of the comparison factor between the groups, and the one-way ANOVA was used to compare the variance of crown analysis regions within the group. A significance level of 5% was considered for the analyses. RESULTS: There was a significant difference between the systems (P = 0.007), with the CS group having the higher mean (23.75 μm ± 3.05) of marginal discrepancy when compared to the open group (17.94 μm ± 4.77). Furthermore, there were no differences in marginal discrepancy between the different points between the groups (P ≥ 0.05). CONCLUSIONS: The studied groups presented results within the requirements set out in the literature. However, the OS used presented better results in marginal adaptation.